2002
DOI: 10.1093/jmicro/51.6.413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enamel matrix derivative on mineralized tissue formation during bone wound healing in rat parietal bone defects

Abstract: Enamel matrix derivative (EMD: Emdogain) has been reported to stimulate the biosynthesis and regeneration of trabecular bone. To address whether the biological action of EMD is dependent on the local environment of osseous tissue, circular perforations were made in parietal bones and immediately filled with either EMD or its carrier, propylene glycol alginate (PGA), as control. On post-operative days 4-60, the dissected bones were examined by various histological techniques. New bone matrix, which was immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The key components improving new bone formation in the present study were the effects of enamel matrix proteins which have been shown to affect new bone formation under various models and also utilizing various carrier systems [20,[31][32][33][34][35]. In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31].…”
Section: Discussionmentioning
confidence: 81%
“…The key components improving new bone formation in the present study were the effects of enamel matrix proteins which have been shown to affect new bone formation under various models and also utilizing various carrier systems [20,[31][32][33][34][35]. In a classical study by Boyan et al, it was shown that although EMD does not possess osteoinductive potential, it possessed osteopromotive benefits when it is combined with active demineralized freeze-dried bone allografts (DFDBA) and resulted in enhanced bone induction [31].…”
Section: Discussionmentioning
confidence: 81%
“…BSP is expressed in hypertrophic chondrocytes [15], and given its effects on endothelial cells migration on the one hand [16] and hydroxyapatite nucleation on the other hand [17], one could expect an effect of the lack of BSP on the onset of endochondral ossification. Surprisingly, this process does not seem to be affected in BSP−/− mice, as no delay appears in the onset of ossification centers, and trabecular BV/TV and osteoclast parameters in newborn femurs are similar between genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While Emdogain has been reported to possess osteopromotive effects on bone healing during repair of bone defects [51,52], other studies have indicated that Emdogain is not truly osteogenic in terms of its ability to induce bone production when implanted into ectopic sites [53,54]. Interestingly, Emdogain has been reported to inhibit the ectopic osteogenic capacity of dentin [53].…”
Section: Discussionmentioning
confidence: 99%